5t-2-3(y+5)=7

Simple and best practice solution for 5t-2-3(y+5)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t-2-3(y+5)=7 equation:


Simplifying
5t + -2 + -3(y + 5) = 7

Reorder the terms:
5t + -2 + -3(5 + y) = 7
5t + -2 + (5 * -3 + y * -3) = 7
5t + -2 + (-15 + -3y) = 7

Reorder the terms:
-2 + -15 + 5t + -3y = 7

Combine like terms: -2 + -15 = -17
-17 + 5t + -3y = 7

Solving
-17 + 5t + -3y = 7

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '17' to each side of the equation.
-17 + 5t + 17 + -3y = 7 + 17

Reorder the terms:
-17 + 17 + 5t + -3y = 7 + 17

Combine like terms: -17 + 17 = 0
0 + 5t + -3y = 7 + 17
5t + -3y = 7 + 17

Combine like terms: 7 + 17 = 24
5t + -3y = 24

Add '3y' to each side of the equation.
5t + -3y + 3y = 24 + 3y

Combine like terms: -3y + 3y = 0
5t + 0 = 24 + 3y
5t = 24 + 3y

Divide each side by '5'.
t = 4.8 + 0.6y

Simplifying
t = 4.8 + 0.6y

See similar equations:

| 12x+21=9-15 | | ln(x-2)=8 | | 7x=-5x+20 | | 4x^2+4x=240 | | 6x+3x+x=100 | | 16+13-8b=-13-14b | | t^2-7tx-30x^2= | | 45+4x=-46-3 | | -x+6y=-28 | | -15.02-9.3c-11.98=-4.3c+17.5 | | -5-10p=-10p-3 | | 4x-9=-45 | | y=0x^2-1.3x+7 | | -4x+10y=-28 | | 1n+2n-4n=20 | | 48n^3=147a | | 48n^2=147n | | 2(x+4)+8=2(-x+12) | | 900/675×9 | | 2x/2=36°/2 | | h=16t^2+50t+50 | | 6-2x/3=1-x | | log[3]3x+log[3]4=log[3]36 | | 9v^2-2v-15=0 | | -7x+3(x+5)=-8x-9 | | 3(w+4)-5w=32 | | 30-2x=12+4x | | 3(x-1)+4=25 | | (8x-9)-(7x-9)= | | 5(5p-5)+7p=167 | | C=0.10x+7 | | 56m^2+376m+240=0 |

Equations solver categories